Development of Physics Laboratory Manual: Characteristic of Resistors Circuit - Ricky Ramdani; Eka Murdani; Intan Kusumawati; Haewoon Park (STKIP Singkawang, 2019)
This study aimed to produce a physics laboratory manual characteristic of a single, series, parallel and series-parallel series of resistors; found out the quality of the physics laboratory manual characteristics of a single, series, parallel and series-parallel series of resistors. This research is a research development. Data collection in this study used suggestion and input sheets, quality assessment sheets for laboratory manual and student response sheets. Laboratory manual quality data obtained from three assessors, student response data for the limited trial I involving six students, and limited trial II involving 28 students. The physics laboratory manual characteristics of a single, series, parallel and series-parallel circuit of resistors have been produced with the criteria of